PENGARUH PROSES BLEACHING TERHADAP SIFAT FISIS DAN MEKANIS KAYU PINUS (Pinus sp.) TERSERANG BLUE STAIN - Wijayanto, Arip; Muhamad, Soleh; Nurhanifah, Nurhanifah; Anggiriani, Siska (Universitas Tanjungpura, 2024)
The weakness of pine wood as a furniture material is that it is easily attacked by blue stain which causes changes in the color of the wood. In previous research, it was reported that bleaching material i.e. sodium hypochlorite 25% had a significant effect on the color change of pine wood affected by blue stain, but the effect on its physical and mechanical properties was not yet known. The aim of this research was to determine the effect of bleaching materials on the physical and mechanical properties of pine wood attacked by blue stain. Bleaching treatment was carried out at three different concentrations, namely a mixture of bleaching material and water 1:1, 1:2, and 2:1. Then the pine woods that has been treated with bleaching were tested for moisture content, density, modulus of elasticity (MOE) and modulus of rupture (MOR)) referring to the BS 372-1957 standard. The test results showed that the bleaching treatment had a significant effect on moisture content, MOE, and MOR, but did not affect density. The moisture content of pine woods attacked by blue stains that were treated with bleaching tended to be higher than the control. Meanwhile, the lowest MOE and MOR values were found in pine wood that was treated with bleaching 2:1.Keywords: bleaching, blue stain, mechanical, pine, physical.AbstrakKelemahan dari kayu pinus sebagai bahan furnitur yaitu mudah terserang blue stain yang menyebabkan terjadinya perubahan warna kayu. Pada penelitian sebelumnya telah dilaporkan bahwa bahan bleaching sodium hipoklorit 25% berpengaruh signifikan terhadap perubahan warna kayu pinus terserang blue stain, namun belum diketahui pengaruh terhadap sifat fisis dan mekanisnya. Penelitian ini bertujuan untuk mengetahui sifat fisis dan mekanis kayu pinus terserang blue stain yang diberi perlakuan bleaching. Perlakuan bleaching pada kayu pinus terserang blue stain dilakukan pada tiga konsentrasi berbeda yaitu campuran bahan bleaching dan air 1:1, 1:2, dan 2:1. Kemudian kayu pinus yang telah diberi perlakuan bleaching diuji kadar air, kerapatan, modulus of elasticity (MOE) dan modulus of rupture (MOR)) mengacu pada standar BS 372-1957. Hasil pengujian menunjukkan bahwa perlakuan bleaching berpengaruh signifikan terhadap kadar air, MOE, dan MOR, namun tidak beroengaruh terhadap kerapatan. Kayu pinus terserang blue stain yang diberi perlakuan bleaching memiliki kadar air yang lebih tinggi dibanding kontrol. Sedangkan nilai MOE dan MOR yang paling rendah ditemukan pada kayu pinus yang diberi perlakuan bleaching 2:1. Kata kunci: bleaching, blue stain, fisis, mekanis, pinus.